2016
DOI: 10.1111/jnu.12195
|View full text |Cite
|
Sign up to set email alerts
|

The Air Quality Health Index and Emergency Department Visits for Otitis Media

Abstract: Clinicians can use the Air Quality Health Index as an education and advocacy tool to promote and protect the health of those at high risk for OM to reduce exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This is a strength of our study; much of the prior literature has relied either on parental self-report 6, 24, 32, 33, 34, 35 or on emergency department visits and hospitalizations 11,15, 20, 23, 36, 37 which do not capture the less-severe morbidities that are treated in pediatric care offices. Even with these clinical records, however, it is very likely that some children had one or more of the outcomes but were never seen by a doctor particularly due to the similar symptoms that these conditions can have to cold or flu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a strength of our study; much of the prior literature has relied either on parental self-report 6, 24, 32, 33, 34, 35 or on emergency department visits and hospitalizations 11,15, 20, 23, 36, 37 which do not capture the less-severe morbidities that are treated in pediatric care offices. Even with these clinical records, however, it is very likely that some children had one or more of the outcomes but were never seen by a doctor particularly due to the similar symptoms that these conditions can have to cold or flu.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in traffic emissions over a 20-year period [1993–2012] were associated with decreases in pediatric bronchitis diagnosis and hospitalizations in Southern California 19 . Modest, positive associations between NO x , PM 2.5, and PM 10 with otitis media among children have been reported in several studies 18, 20, 21,22,23 but not others 11,24 .…”
Section: Introductionmentioning
confidence: 91%
“…The research findings confirm that there is direct correlation between the AQHI and the emergency department visits for Otitis Media. (33) Application of Hong Kong equation on the selected street in Alexandria, Egypt revealed values AQHI more than 3.5 times higher than that found in China. (20) This necessitates developing an Egyptian equation to enable better justification of the Egyptian situation, and to enhance the decision-making process.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, epidemiological evidence supports the link between air pollution and ASOM. Many studies have reported health effects of O 3 has a strong potentially adverse health effects on various respiratory symptoms such as, dyspnea, upper airway irritation, coughing, and chest tightness [22].However, no significant association between O 3 and the prevalence of ASOM was observed in Lanzhou. Research on harmful effects of O 3 is rare in China, so further studies are needed.…”
Section: Ambient Air Pollution and Asommentioning
confidence: 96%